Carbon streaming in microalgae: extraction and analysis methods for high value compounds. (November 2017) - Venkata Subhash, G.; Rajvanshi, Meghna; Navish Kumar, B.; Govindachary, Sridharan; Prasad, Venkatesh; Dasgupta, Santanu
Graphical abstract: Highlights: Review describes modes of carbon streaming towards various metabolites under different growth conditions. Also pros and cons of various algal cultivation methods were described. Metabolic pathways involved in the biosynthesis of high value compounds were discussed. Comprehensive review on high throughput technologies for extraction and analysis of bio-molecules from algae. Abstract: There is a growing recognition that carbon-neutral biofuels and microalgae are eco-friendly options because of their high CO2 sequestering capability and ability to grow in wastewater/sea water and non-arable land. Also the intrinsic properties of microalgal systems can be exploited for high value compounds such as carbohydrates, lipids, pigments and proteins. This article provides a comprehensive review of various microalgae cultivation practices utilizing organic and inorganic carbon sources. The merits and demerits of the various extraction and analytical procedures have also been discussed in detail.